1994
DOI: 10.2527/1994.7261455x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting excretory behavior of pigs

Abstract: A 2(4) factorial experiment with six pens per treatment was conducted to examine the factors affecting the excretory behavior of growing-finishing pigs. The factors investigated were partition type (open or closed), pig density (9 or 14 pigs/pen, size: 2 m x 4.5 m), position of nipple drinker in the pen (back wall of the pen or side in front of slatted area), and prior experience of pigs (training or no training). A total of 1,104 pigs at a weight interval of 28.4 +/- .2 to 91.4 +/- .4 kg were used in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 4 publications
2
61
1
1
Order By: Relevance
“…If possible, pigs excrete in a localized part of their pen and prefer to separate their dunging area from their lying area (Meunier-Salaü n, 1989;Hacker et al, 1994). If pigs are dirty with faeces, it is because some factors have temporarily forced them to lie in their excrement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If possible, pigs excrete in a localized part of their pen and prefer to separate their dunging area from their lying area (Meunier-Salaü n, 1989;Hacker et al, 1994). If pigs are dirty with faeces, it is because some factors have temporarily forced them to lie in their excrement.…”
Section: Discussionmentioning
confidence: 99%
“…Older pigs spend more time lying and they are more likely to adopt a fully recumbent position (Ekkel et al, 2003). Moreover, several studies on pigs in conventional conditions have found that dunging on the solid floor increases when pigs are heavier (Hacker et al, 1994). Thereafter, a higher evaporative heat loss in heavy pigs in addition to a greater space occupational area may increase the probability of an older pig lying on a dunging area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the current study we did not observe an effect of slatted floor percentage on MORT. In any case, the optimal proportion of slated floor should be related to the density of pigs in the pen, since pigs use specific areas of the pen to feed, rest and defecate, where resting in a dry and solid floor is a priority (Hacker et al, 1994). In addition, differences observed in FCR but not in MORT could be explained by the greater probability to lose feed through the slats leading to a greater feed wastage in pens with >50% slatted floor.…”
Section: Alsomentioning
confidence: 99%
“…In Sweden, pens for pigs have a solid resting area, in contrast to most European countries where fully slatted floor pens are allowed (Mul et al, 2010). Defecation and urination will normally not occur in the resting area (Wechsler, 1996;Horsted et al, 2012) as animals prefer a warm lying area and a cooler area for dunging during normal and cold temperatures (Hacker et al, 1994). However, at warmer temperatures, pigs spend more time in cooler places in the pen, which is usually the dunging area (Botermans and Andersson, 1995).…”
Section: Introductionmentioning
confidence: 99%